INDO-US STRATEGIC RELATIONS IN 21ST CENTURY - Singh, Balwinder (International Journal of Research -GRANTHAALAYAH, 2017)
The disintegration of Soviet Union had positively impacted Indo-US relations in post Cold-War era. The post Cold-War strategic scenario provided a chance to both countries to redefine their bilateral priorities. The US was always keen to improve bilateral relationship with India and therefore India initiated Defence cooperation with the US in changing strategic environment. India’s nuclear explosion [1998] had posed some divergences in Indo-US relationship. India and the US signed strategic partnership in 2000 and therefore the US set-aside its sanctions against India. India signed ‘Next Steps in Strategic Partnership’ [NSSP] with the US in 2004 and both countries started strategic dialogue in 2009. Both the nations signed a ‘New Framework for Defence Relationship’ in 2005 and ‘123 Civil Nuclear Agreement’ in 2008. India has always supported US’s ‘pivot-aria’ policy and played a meaningful role in counter China strategy. India and the US renewed their ‘New Framework for Defence Relationship’ in 2015 and signed ‘Logistic Support Agreement’ in 2016. Indo-US strategic relations were touched new heights when the Obama administration had declared India as a major Defence partner in 2016. The new US President Trump also showed its softness towards India and called Indian Prime Minister Modi as a ‘True Friend of US’. The decline of US-Pakistan strategic relations has positively affected Indo-US relations. The Pakistan factor has always affected Indo-US relations. The US administration considers that India would play a meaningful role in counter China planning. The study explores the raison d’être of Indo-US strategic partnership. The present paper intends to look into the Indo-US strategic cooperation and points out the improvement in Indo-US strategic relations in 21st century.